RELATIONSHIP BETWEEN AGE AND STAGE LEVEL WITH THE INCIDENT OF DEATH IN CA MAMAE PATIENTS AT M. YUNUS HOSPITAL, BENGKULU CITY. - Ezza febriya lopa; Diah Eka Nugraheni; Elly Wahyuni (Poltekkes Kemenkes Banten, 2026)
Ca mamae is one of the leading causes of morbidity and mortality among women worldwide, including in Indonesia. Data from M. Yunus Hospital, Bengkulu, showed an increasing number of breast cancer cases between 2022 and 2024, along with a rise in mortality rates. Age and cancer stage are assumed to be associated with mortality among breast cancer patients. This study aimed to determine the relationship between age and cancer stage with mortality in breast cancer patients at M. Yunus Hospital, Bengkulu, in 2022–2024. This research employed an analytic case-control design. A total of 96 patients were included, consisting of 48 deceased patients (cases) and 48 surviving patients (controls) selected using total sampling and random sampling methods. Data were obtained from medical records and analyzed using Chi-Square and logistic regression tests. The results showed that most deceased patients were >40 years old (75%) and nearly all were in advanced stages (III–IV) (97.9%). Bivariate analysis revealed no significant relationship between age and mortality (p=0.451; OR=0.600). Conversely, there was a significant association between cancer stage and mortality (p<0.001; OR=55.000). In conclusion, age was not significantly associated with breast cancer mortality, whereas cancer stage showed a strong association. Early detection and treatment at earlier stages are crucial to reducing breast cancer mortality.